2014
DOI: 10.1016/j.cortex.2014.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Experience in judging intent to harm modulates parahippocampal activity: An fMRI study with experienced CCTV operators

Abstract: Does visual experience in judging intent to harm change our brain responses? And if it does, what are the mechanisms affected? We addressed these questions by studying the abilities of Closed Circuit Television (CCTV) operators, who must identify the presence of hostile intentions using only visual cues in complex scenes. We used functional magnetic resonance imaging to assess which brain processes are modulated by CCTV experience. To this end we scanned 15 CCTV operators and 15 age and gender matched novices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 93 publications
2
15
0
Order By: Relevance
“…ISC analysis has been used with fMRI to study a variety of topics, such as memory (Hasson et al, 2008a;van Kesteren et al, 2010), temporal receptive fields (Hasson et al, 2008c), communication (Hasson et al, 2012) and auditory processing of music (Abrams et al, 2013). It has also been used to identify group differences in autism (Hasson et al, 2009), schizophrenia (Kim et al, 2008), development (Cantlon and Li, 2013) and experience in action observation (Petrini et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ISC analysis has been used with fMRI to study a variety of topics, such as memory (Hasson et al, 2008a;van Kesteren et al, 2010), temporal receptive fields (Hasson et al, 2008c), communication (Hasson et al, 2012) and auditory processing of music (Abrams et al, 2013). It has also been used to identify group differences in autism (Hasson et al, 2009), schizophrenia (Kim et al, 2008), development (Cantlon and Li, 2013) and experience in action observation (Petrini et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These behavioural differences are in 6 conjunction with differences in brain activity as revealed by fMRI data using a whole 7 brain analysis of experienced operators and novices when they viewed 16 second 8 clips of different intentions. Results of this study showed decreased activity in the 9 anterior parahippocampal gyrus of operators suggesting more efficient neural 10 processing in judging hostile intentions (Petrini et al, 2014). represented by brief point light displays (Johansson, 1973).…”
Section: Introductionmentioning
confidence: 74%
“…As a consequence, behavioural and 1 fMRI studies have been conducted to investigate the effects of expertise on viewing 2 and evaluating CCTV footage. Evidence suggests that experienced operators, 3 compared to novices use a more systematic pattern of eye movements (Roffo et al,4 2013) when scanning scenes and exhibit higher sensitivity in judgments of hostile 5 intent and suspiciousness (Petrini et al, 2014). These behavioural differences are in 6 conjunction with differences in brain activity as revealed by fMRI data using a whole 7 brain analysis of experienced operators and novices when they viewed 16 second 8 clips of different intentions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the higher ability of experienced operators in predicting violence in surveillance footage [12], we argue that understanding the way visual information is processed can be important for automated video surveillance.…”
Section: Introductionmentioning
confidence: 99%